Potential Natural Products Against Respiratory Viruses: A Perspective to Develop Anti-COVID-19 Medicines - Omrani, Marzieh; Keshavarz, Mohsen; Nejad Ebrahimi, Samad; Mehrabi, Meysam; McGaw, Lyndy J.; Ali Abdalla, Muna; Mehrbod, Parvaneh (Frontiers in Pharmacology, 2021)
The emergence of viral pneumonia caused by a novel coronavirus (CoV), known as the 2019 novel coronavirus (2019-nCoV), resulted in a contagious acute respiratory infectious disease in December 2019 in Wuhan, Hubei Province, China. Its alarmingly quick transmission to many countries across the world and a considerable percentage of morbidity and mortality made the WHO recognize it as a pandemic on March 11, 2020. The perceived risk of acquiring disease has led many research groups to study COVID-19 from different aspects. We provide here a brief review of 2019-nCoV and summarized knowledge about the pathogen and the current pandemic. In this literature review, phylogenetics and taxonomy of COVID-19 coronavirus, epidemiology, and respiratory viruses similar to COVID-19 and their mode of action are reviewed. Additionally, since phytochemicals play an essential role in complementary therapies for viral infections, we reviewed bioactive natural products against mentioned respiratory viruses with a focus on influenza A, SARS-CoV, MERS, and COVID-19. Additionally, with consideration of the provided information, we discussed the obstacles and future perspectives to highlight the importance of developing screening programs to investigate potential natural medicines against COVID-19.